Seroprevalensi Toksoplasmosis di Kabupaten Gianyar, Bali - Ni Putu Eka Febianingsih; Citra Indriani; Wayan Tunas Artama (Fakultas Kedokteran Universitas Gadjah Mada, 2017)
Seroprevalence of human toxoplasmosis in Gianyar Bali provincePurposeThe present study was designed to determine the seroprevalence and risk factors of human toxoplasmosis.MethodsThe research used a cross-sectional design and was conducted in Gianyar District, Bali Province. A total of 240 sera samples were collected and examined by indirect ELISA methods for IgG Anti-T. gondii. Demographic characteristics and risk factors were collected by interviews using a structured questionnaire. Data were analysed using the Poisson regression test with robust variance estimators.ResultsSeroprevalence of human toxoplasmosis in Gianyar District were 56.7%. Multivariate analysis showed that there was an association between meal of raw meat/Lawar (aPR: 1.40; 95%CI: 1.05-1.86); Male (aPR1:42; 95%CI: 1.12-1.81); existence of animals/wild cats (aPR: 1.48; 95%CI: 1.04-2.09); often washing their hand (aPR: 1.25; 95% CI: 1.01-1.56); elevation (aPR: 0.99; 95%CI: 0.99-0.99); and distance to the river from the house (aPR: 0.99; 95%CI: 0.99 to 0.99).ConclusionThere was found high seropositive toxoplasmosis in Gianyar District. Patients with seropositive toxoplasmosis should receive treatment and health information. There should be continued prevention efforts to increase health knowledge about toxoplasmosis and transmission.